Determining the Molecular Shape of Progesterone: Insights from Laser Ablation Rotational Spectroscopy - Insausti, Aran; Alonso, Elena R; Municio, Sofía; León, Iker; Kolesniková, Lucie; Mata, Santiago (The journal of physical chemistry letters, 2025)
Herein, we present the first experimental observation of isolated progesterone, an endogenous steroid, placed in the gas phase by laser ablation and characterized in a supersonic expansion by Fourier transform microwave techniques. Guided by quantum-chemical calculations, we assigned the rotational spectrum of the most stable structure. The internal rotation of the acetyl methyl group led to the observation of A-E doublets in the spectrum, which were analyzed, resulting in a V3 barrier of 2.4425 ± 0.0025 kJ mol-1. By fitting over 250 transitions, we determined accurate rotational constants that enabled us to compare the gas phase geometrical parameters with those of crystalline forms and complexes with progesterone receptors. Our results indicate that the A ring of progesterone that contains the ketone group is surprisingly flexible, despite its rigid appearance. This finding is particularly significant, since this ring is an active biological site that is involved in strong intermolecular interactions. Notably, progesterone C21H30O2 is the largest molecule investigated using laser ablation rotational spectroscopy.